Pendampingan Usaha Mikro Kecil dan Menengah (UMKM) Peternakan Telur Itik Guna Meningkatkan Daya Jual Telur Itik - Hendrika, Yan; Mutiara; Widia Fransiska; Rozi Thoyyiba Tampi; Athilya Putri; Jihan Farisa; Andre; Andini Sinaga; Rahmayani; Sandra Sept; Abdul Aziz; Titok Wilyanzah; Nur Fika Herlina; Sartika Dewi; Rhamadani, Fitrah (Yayasan Rahmatan Fidunya Wal Akhirah, 2023)
Micro, small and medium enterprises (MSMEs) have a very important role in driving development and growth and the economy, both in developing and developed countries (Chrismardani, 2014). MSMEs are the right choice for the community to improve economic conditions. The main objective is to collect comprehensive data related to MSMEs in the area in an effort to improve the economy and sustainability of MSMEs in Sungai Pinang Village, as well as to seek to select MSMEs that have significant potential to increase their selling power. In order to be able to identify, understand, and develop MSMEs that have better growth opportunities in the context of Sungai Pinang Village. Ujang/Syahrul's duck egg farm in Sungai Pinang, Tambang District, Kampar Regency, Riau Province, is the only duck farm in the area. A group of 24 KKN students from Abdurrab University chose this business as an MSME program because of its remote location and the lack of public knowledge about it, while the community's interest in duck eggs and meat is high. Their initial steps were to conduct a location survey, ask permission from the business owner, and adopt online marketing methods and placing banners as a promotional strategy. The positive impact was a significant increase in sales of duck eggs and meat, even extending beyond Sungai Pinang.